Revision for the Rapid Emergency Triage and Treatment System Adult (RETTS-A) needed?. Issue 1 (December 2016) - Mirhaghi, Amir; Christ, Michael
Abstract The study highlights the prognostic role of patient's vital signs at presentation to the emergency department (ED): The predictive role of vital signs in ED triage has been controversially discussed probably due to a paucity of data on the value of vital signs in ED at presentation. However, the authors did not find a suitable way to adjust for the inherent influence of triage decision and medical treatment on mortality. We have discussed that ambiguity concerning the assessment of vital signs criteria in RETTS-A Red priority may threaten any association between patient acuity and fatal outcome.